(Supra)National Identity and Language: Rethinking National and European Migration Policies and the Linguistic Integration of Migrants. (13th March 2015) - Wodak, Ruth; Boukala, Salomi
ABSTRACT: In this paper we juxtapose the European Union's (EU's) supranational policies on language and migration with their recontextualisation into national policies of the linguistic integration of migrants in two EU member states, Austria and Greece. The EU member states adapt the European legislation according to their national laws ( National Acton Plans ) which have to also account for national traditions and national citizenship legislation. Moreover, we explore the national regulations on language testing and the linguistic integration of migrants in Austria and Greece which are part and parcel of the National Action Plans and which establish obstacles for migrants: Indeed, they function as gate-keepers. Hence, a context-dependent micro-level discourse analytic approach suggests itself. The data for the analysis stem from legal and policy texts of the EU, Austria and Greece (regulations on citizenship, language education, testing and the linguistic integration of migrants). By employing the Discourse Historical Approach (DHA) of Critical Discourse Studies we analyze how specific EU regulations are implemented in national legislation; how migrants, who live in Austria and Greece are represented by the legislators, and finally how the respective national identities in the context of migration legislation are constructed.